2022
DOI: 10.1523/jneurosci.2123-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical Mechanisms for Nostalgia-Induced Analgesia

Abstract: As a predominately positive emotion, nostalgia serves various adaptive functions, including a recently revealed analgesic effect. The current fMRI study aimed to explore the neural mechanisms underlying the nostalgia-induced analgesic effect on noxious thermal stimuli of different intensities. Human participants' (males and females) behavior results showed that the nostalgia paradigm significantly reduced participants' perception of pain, particularly at low pain intensities. fMRI analysis revealed that analge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, college students who did not suffer from pain disorders were able to tolerate higher levels of applied pressure (i.e., showed higher pain tolerance) after writing about a nostalgic event (Kersten et al, 2020). This analgesic effect of nostalgia was recently confirmed in an fMRI study that showed participants images of objects or scenes designed to elicit nostalgic feelings of their childhood or to remind them of modern life (Zhang et al, 2022). During the viewing of the images that cued memories of childhood, participants reported more nostalgia, and when a painful stimulus followed those images, participants perceived it as less painful than when it followed the cues to modern life.…”
Section: Positive Memories Retain Their Affective Strength and Act As...mentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, college students who did not suffer from pain disorders were able to tolerate higher levels of applied pressure (i.e., showed higher pain tolerance) after writing about a nostalgic event (Kersten et al, 2020). This analgesic effect of nostalgia was recently confirmed in an fMRI study that showed participants images of objects or scenes designed to elicit nostalgic feelings of their childhood or to remind them of modern life (Zhang et al, 2022). During the viewing of the images that cued memories of childhood, participants reported more nostalgia, and when a painful stimulus followed those images, participants perceived it as less painful than when it followed the cues to modern life.…”
Section: Positive Memories Retain Their Affective Strength and Act As...mentioning
confidence: 87%
“…FMRI results revealed that connectivity between the dorsolateral PFC and periaqueductal gray (a region linked to pain and analgesia; Linnman et al, 2012;Grahl et al, 2018) during the viewing of the nostalgic images related to this diminished perception of pain. Taken together, these studies suggest the fascinating possibility that retrieval of a positive memory can have retrograde and anterograde effects, minimizing the negative impacts of a just-experienced event or an about-to-be experienced event (Zhang et al, 2022).…”
Section: Positive Memories Retain Their Affective Strength and Act As...mentioning
confidence: 88%
“…A priori power analysis indicated that a sample size of 34 would allow for the detection of medium effect size (d = 0.25) with 80% power at an alpha of 0.05 for the repeated measures with two within-subject factors, according to the previous study. 40 participants not to ingest any alcohol or pain medicine for at least 4 h prior to participating in the experiment. 35,36 Participants completed a thorough written informed consent process and were compensated and debriefed after completing all the tasks.…”
Section: Participantsmentioning
confidence: 99%
“…A total of 66 participants took part in study 2 (29 males, age = 21.82 ± 1.98 years, range = 18-26 years). These participants comprised samples from two separate studies to expand our total sample size (n = 32 and n = 34) to achieve more stable results; one was an fMRI study conducted in the same experimental setup but focused on different research purposes (i.e., brain mechanisms of analgesia) 40. There was no significant difference in pain sensitivity (t(64) = 1.19, p = 0.237), nostalgic proneness (t(64) = 0.55, p = 0.583), reported pain (t(64) = 0.11, p = 0.915), and nostalgic strength (t(64) = 1.09, p = 0.278) /pleasantness (t(64) = −0.24, p = 0.813) toward figure stimuli between the two studies, suggesting that participants were homogeneous and could be combined.…”
mentioning
confidence: 99%
“…From a psychological standpoint, momentary nostalgia increases self‐esteem (Hepper et al, 2012; Vess et al, 2012; Wildschut et al, 2006), optimism (Cheung et al, 2013; Evans et al, 2021; Reid et al, 2015), inspiration (Evans et al, 2021; Hinsch et al, 2020; Stephan et al, 2015), self‐continuity (Hong et al, 2021, 2022; Sedikides, Wildschut, Routledge, & Arndt, 2015), meaningfulness (Hepper et al, 2012; Routledge et al, 2011; Van Tilburg et al, 2013), and social support (Lasaleta et al, 2021; Routledge et al, 2011; Zhou et al, 2008) or social connectedness (Evans et al, 2021; Hepper et al, 2012; Wildschut et al, 2006). Additionally, momentary nostalgia eases physical distress by fostering a sense of physiological comfort (Zhou et al, 2012) and curtailing perceptions of pain (Kersten et al, 2020; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%